The experiences of motherhood amog black undergraduate students at a South African university: reconciling competing roles - Maisela, Thato (My University, 2016)
Although there are no official statistics available on the number of students falling pregnant while pursuing their undergraduate degrees, anecdotal evidence suggests that the prevalence is likely to be under-reported. While educational policy gives all persons the right to attend educational institutions irrespective of pregnancy or maternal status, it can be demanding to be both a student and mother and to reconcile competing conceptions, particularly within African culture, of what it means to be a ‘good student’ and a ‘good mother’. The research adopted the perspectives of feminism and gender role theory to explore the challenges that University level mothers experience and the strategies they adopt to cope with their situations and reconcile these competing roles. The study was located within an interpretive, qualitative research paradigm and involved semi-structured interviews with a purposive sample of 15 female undergraduate university students. Data were analysed using thematic content analysis. Key findings that emerged were that the student mothers that were interviewed experienced financial, social and emotional challenges. However, they were able to cope through the support of family and friends. These findings have implications for the support and empowerment of student mothers through social work practice and university interventions. Key Words: student mothers, university, gender, role conflict